A case report of Becker’s variety of myotonia congenita - Khan, Nurul Amin; Wadud, Shaheen; Islam, Torikul; Ghosh, Liton Chandra (Journal of Dhaka National Medical College & Hospital, 2022)
Myotonia congenita is a disease of skeletal muscle. It usually begins at childhood and problem in muscle relaxation after contraction of muscles. It involves lower limb muscles more than any other group of muscles. It causes muscle stiffness and interfere with movement like walking, running and other daily activities. Our case was a thirteen years old Muslim male presented with history of stiffness and transient weakness. On examination we found that myotonia in grip, tongue and other muscles with hypertrophy of the proximal muscle and myotonia was more marked on lower limbs. CPK was mildly raised, electro-physiological test showed typical dive bomber's myotonic discharge and muscle biopsy showed the myopathy. On later presentation, more severe disease and marked hypertrophy of proximal muscle established the recessive Becker type of myotonia. Explanation of the nature of disease with symptomatic treatment by phenytoin, improved the patient symptoms. Familial counselling about this disease had also been carried out. J. Dhaka National Med. Coll. Hos. 2022; 28 (02): 45-48